2020
DOI: 10.1016/j.joca.2020.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Associations of trochlea morphology and patellofemoral alignment with prevalent radiographic patellofemoral osteoarthritis

Abstract: Objective: To investigate the relation of trochlea morphology and patellofemoral alignment to prevalent radiographic patellofemoral osteoarthritis (PFOA). Design: A within-person knee-matched case-control study was performed. Participants with unilateral radiographic PFOA were selected from the Multicenter Population-based Osteoarthritis Study (MPOA) in three towns in northern China that was approved by Peking University Health Science Center Ethics Committee (2018PHB166-01). Radiographic PFOA, radiographic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In this study, type III patellar morphology is associated with more severe lateral PFOA. A previous study showed that Wiberg patella type III, which presented a medial border dysplasia or a short patellar apex, is more often involved in patients with patellar dislocation [ 29 ], and patella lateral displacement is associated with more severe lateral PFOA [ 30 ]. On the other hand, Wiberg type III patella presented only a small amount of contact with the medial femoral condyle due to the low surface area of the medial facet, which increased the contact pressure of the lateral patella facet on the lateral femoral condyle during knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, type III patellar morphology is associated with more severe lateral PFOA. A previous study showed that Wiberg patella type III, which presented a medial border dysplasia or a short patellar apex, is more often involved in patients with patellar dislocation [ 29 ], and patella lateral displacement is associated with more severe lateral PFOA [ 30 ]. On the other hand, Wiberg type III patella presented only a small amount of contact with the medial femoral condyle due to the low surface area of the medial facet, which increased the contact pressure of the lateral patella facet on the lateral femoral condyle during knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, type III patellar morphology is associated with more severe lateral PFOA. A previous study showed that Wiberg patella type III, which presented a medial border dysplasia or a short patellar apex, are more often involved in patients with patellar dislocation [29], and patella lateral displacement is associated with more severe lateral PFOA [30]. On the other hand, Wiberg type III patella presented only a small amount of contact with the medial femoral condyle due to the low surface area of the medial facet, which increased the contact pressure of the lateral patella facet on the lateral femoral condyle during knee exion.…”
Section: Discussionmentioning
confidence: 99%
“…It can develop in isolation or in combination with tibiofemoral osteoarthritis (TFOA). The patellofemoral joint (PFJ) has a unique configuration, so its susceptibility to developing symptoms of knee OA is higher than that in patients with TFOA (16). The treatment options for patients with PFOA vary according to the location of the lesion and degree of joint derangement (4,7).…”
Section: Introductionmentioning
confidence: 99%